2005
DOI: 10.1016/j.aim.2004.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Generalised discriminants, deformed Calogero–Moser–Sutherland operators and super-Jack polynomials

Abstract: It is shown that the deformed Calogero-Moser-Sutherland (CMS) operators can be described as the restrictions on certain affine subvarieties (called generalised discriminants) of the usual CMS operators for infinite number of particles. The ideals of these varieties are shown to be generated by the Jack symmetric functions related to the Young diagrams with special geometry. A general structure of the ideals which are invariant under the action of the quantum CMS integrals is discussed in this context. The shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
160
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(164 citation statements)
references
References 24 publications
3
160
0
1
Order By: Relevance
“…This type of generalisation is integrable in the case of two types of particles [6], [24]. More remarkably, Sergeev and Veselov showed that the corresponding quantum Hamiltonian can be obtained by applying a restriction procedure on the Calogero-Moser-Sutherland Hamiltonian in the infinite dimensional space to the appropriate discriminant [25]. We plan to elaborate these relations in future.…”
Section: Introductionmentioning
confidence: 88%
“…This type of generalisation is integrable in the case of two types of particles [6], [24]. More remarkably, Sergeev and Veselov showed that the corresponding quantum Hamiltonian can be obtained by applying a restriction procedure on the Calogero-Moser-Sutherland Hamiltonian in the infinite dimensional space to the appropriate discriminant [25]. We plan to elaborate these relations in future.…”
Section: Introductionmentioning
confidence: 88%
“…The proof is effective but not conceptual. We present more conceptual proof for A(n, m) series in our paper [38], where the algebraic varieties corresponding to the rings Λ 0 R,B and relations with the theory of Jack polynomials are also discussed in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…The relation with the theory of Jack polynomials is actually much deeper. We discuss this in detail in our paper [38] (see also [13], [14]). …”
Section: Construction Of Quantum Integrals For Classical Seriesmentioning
confidence: 99%
“…The Fourier transforms a c (k) of these operators, and their hermtian conjugates, defined as in (40) and (43), obey the commutation relations…”
Section: The Multi-species Generalizationmentioning
confidence: 99%
“…The authors of [39] introduced deformed Calogero models, related to root systems of superalgebras, and gave effectively a proof of their integrability. In [40] they presented a more conceptual proof by using shifted super-Jack polynomials. In related developments, the authors of [41,42] introduced a supersymmetric generalizations of the CM which was based on Jacobians for the radial coordinates on certain superspaces.…”
Section: Introductionmentioning
confidence: 99%